Co-immobilization of Chaetoceros calcitrans MZB-1 and culture medium in alginate beads for bioremediation of perfluorooctanoic acid and perfluorooctanesulfonic acid in seawater - Wenlu Li; Fanping Meng (Bioresource Technology, 2027)

Identification and induction of key oxygenases involved in the degradation of propylbenzenes by Chaetoceros calcitrans MZB-1 - Wenlu Li; Yu Leng; Fanping Meng (Journal of Environmental Chemical Engineering, 2026)

Biodegradation mechanisms of p-xylene by the oceanic microalga Rhodomonas sp. JZB-2 through transcriptomics and metabolomics - Wenlu Li; Fanping Meng; Hao Li; Houlei Li; Wenjia Sun (Bioresource Technology, 2026)

Enhanced degradation of n-propylbenzene and isopropylbenzene in seawater through microalga-microalga consortium: Combination screening, inoculation ratio, kinetics, and degradation mechanisms - Wenjia Sun; Yumei Li; Fanping Meng; Houlei Li; Wenlu Li (Marine Pollution Bulletin, 2026)

Biodegradation of perfluorooctanoic acid and perfluorooctanesulfonic acid by a marine microalga Chaetoceros calcitrans MZB-1: kinetic analysis, removal pathways, and effects of environmental factors - Wenlu Li; Fanping Meng; Wenjia Sun (Journal of Environmental Management, 2026)

Biodegradation pathways and mechanisms of perfluorooctanoic acid and perfluorooctanesulfonic acid via key enzymes in the marine microalga Chaetoceros calcitrans MZB-1 - Wenlu Li; Fanping Meng; Wenjia Sun (Journal of Hazardous Materials, 2025)

Natural attenuation mechanisms and ecological safety of perfluorooctanoic acid and perfluorooctanesulfonic acid in simulated marine conditions - Wenlu Li; Fanping Meng (Journal of Environmental Chemical Engineering, 2025)

Diatom Chaetoceros calcitarans MZB-1 for degrading propylbenzenes in seawater: Cultivation conditions, degradation kinetics, and influencing factors - Yu Leng; Yumei Li; Fanping Meng; Wenjia Sun (Marine Environmental Research, 2025)

A laccase-dual mediator system constructed for degrading n-propylbenzene and isopropylbenzene from seawater: Influencing factors, kinetics, mechanism, and eco-toxicity evaluation - Shan Chen; Fanping Meng (Journal of Environmental Chemical Engineering, 2025)

Microplastics in marine systems: A review of sources and sinks, typical environmental behaviors, and biological effects - Wenlu Li; Fanping Meng (Marine Pollution Bulletin, 2025)

Biodegradation of 1,2,4-trimethylbenzene in seawater using Rhodomonas sp. JZB-2: Performance, kinetics, and mechanism - Haiping Li; Fanping Meng; Yu Leng (Journal of Environmental Management, 2025)

Performance, kinetics, and mechanism of 1,2,3-trimethylbenzene biodegradation by a newly isolated marine microalga - Haiping Li; Fanping Meng; Shuhao Du; Jiali Cui (Journal of Environmental Management, 2025)

Metabolic variation and oxidative stress responses of clams (Ruditapes philippinarum) perturbed by ofloxacin exposure - Bo Zhang; Xiaotong Wang; Fanping Meng; Shuhao Du; Haiping Li; Yufan Xia; Yu Yao; Ping Zhang; Jiali Cui; Zhengguo Cui (Journal of Hazardous Materials, 2024)

An efficient nonlocal integral method based on the octree algorithm - Dechun Lu; Yaning Zhang; Xin Zhou; Fanping Meng; Cancan Su; Xiuli Du (Computers and Geotechnics, 2024)

Modeling confined concrete behavior in finite element with a non-orthogonal elastoplastic model - Fanping Meng; Dechun Lu; Shanyong Wang; Xin Zhou; Xiuli Du (Engineering Structures, 2024)

Effects of inorganic nutrients and environmental factors on the removal of n-propylbenzene and isopropylbenzene in seawater by cryptophytes Rhinomonas reticulata S6A - Jiali Cui; Shuhao Du; Yumei Li; Haiping Li; Ping Zhang; Fanping Meng (Journal of Oceanology and Limnology, 2024)

Construction of a continuous packed bed laccase reactor for the elimination of tetracyclines in seawater - Xiaotong Wang; Fanping Meng (Journal of Environmental Chemical Engineering, 2024)

Adsorption, natural attenuation, and microbial community response of ofloxacin and oxolinic acid in marine sediments - Haiping Li; Bo Zhang; Fanping Meng; Siyuan Shao; Yufan Xia; Yu Yao (Environmental Pollution, 2024)

Detection and dietary risk of per- and polyfluoroalkyl substances in shellfish products from the coasts of Bohai Sea and South China Sea - Linfeng Wu; Jiangbing Qiu; Aifeng Li; Ying Ji; Guowang Yan; Fanping Meng (Chemosphere, 2024)

Emergency response to ecological protection in maritime phenol spills: Emergency monitor, ecological risk assessment, and reduction - Haiping Li; Fanping Meng; Yu Leng; Aifeng Li (Marine Pollution Bulletin, 2024)

Deriving seawater quality criteria of tris(2-chloroethyl) phosphate for ecological risk assessment in China seas through species sensitivity distributions - Ping Zhang; Fanping Meng; Yufan Xia; Yu Leng; Jiali Cui (Journal of Environmental Management, 2024)

Comparative study of in-situ formation process of Mg-Al layered double hydroxides though two pathways to remove Cr(VI) and As(V) from wastewater - Yuan Xie; Hanhan Huang; Zihan Zhang; Yu Wang; Fanping Kong; Zequn Ma; Huiqiang Liu; Zilin Meng (Journal of Environmental Chemical Engineering, 2023)

Efficiency, mechanism, influencing factors, and integrated technology of biodegradation for aromatic compounds by microalgae: A review - Haiping Li; Fanping Meng (Environmental Pollution, 2023)

Elimination of tetracyclines in seawater by laccase-mediator system - Xiaotong Wang; Fanping Meng; Bo Zhang; Yufan Xia (Chemosphere, 2023)

Colloidal Gold Immunochromatographic Assay for Rapid On-Site Detection of Tetracycline in Seawater - Haiping Li; Fanping Meng; Aifeng Li (Journal of Ocean University of China, 2023)

Marine ecological risk assessment for the herbicide sulfometuron-methyl based on species sensitivity distribution approach - Jiaqi Liu; Fanping Meng; Shuhao Du; Siyuan Shao (Journal of Oceanology and Limnology, 2023)

Bioremediation of propylbenzenes by a novel marine microalga Rhinomonas reticulata S6A isolated from Daya Bay: acute toxicity, growth kinetics and biodegradation performance - Shuhao Du; Jiali Cui; Fanping Meng; Haiping Li; Hongwu Cui; Yufan Xia (Frontiers in Marine Science, 2023)
This study investigated the degradation characteristics of propylbenzenes (PBZs, including isopropylbenzene and n-propylbenzene), with high leakage risks and ecological hazards, by a newly isolated marine microalga named Rhinomonas reticulata S6A which is a promising candidate for eco-friendly bioremediation from marine. About 72% and 56% of n-PBZ and i-PBZ can be degraded after 7 days in culture. The acute toxicity of n-PBZ (96h - EC 50 = 2.38 mg/L) was higher than that of i-PBZ (96h - EC 50 = 3.65 mg/L). The growth inhibition kinetics of this strain were consistent with the Edwards model ( R 2 = 0.998) and Aiba model ( R 2 = 0.999). The optimal concentrations for the degradation of n-PBZ and i-PBZ were calculated to be 2.42 mg/L and 2.78 mg/L, respectively. The degradation trends of PBZs conformed to the zero-order kinetic model, and k increased with initial concentrations. The moderate increase in inoculation density could accelerate the degradation of PBZs, with the maximum specific growth rates ( r ) of 1.116/d (n-PBZ) and 1.230/d (i-PBZ) at the initial inoculation density of 10 4 cells/mL, while over-inoculation (initial microalgae density more than 10 5 cells/mL) was not conducive to the degradation of the pollutants. There is not much data on the biodegradation of PBZs in the aquatic environment, so it would be worthwhile to try to apply the new microalgae to explore the fate of PBZs.

High-efficiency removal of antibiotics through self-assembly formation of layered double hydroxides in wastewater - Yuan Xie; Fanping Kong; Zhiwei Mi; Hanhan Huang; Caifeng Xia; Zequn Ma; Shuang Li; Qian Zhang; Zilin Meng (Journal of Water Process Engineering, 2023)

An effective strategy for removing tetracycline from water: Enhanced adsorption reliability and capacity by tyrosine modified layered hydroxides - Caifeng Xia; Xiangming Li; Yuan Xie; Fanping Kong; Menglan Zhao; Yu Wang; Yang Wang; Qian Zhang; Zilin Meng (Journal of Environmental Chemical Engineering, 2023)

Putative biosynthesis mechanism of the neurotoxin β-N-methylamino-L-alanine in marine diatoms based on a transcriptomics approach - Aifeng Li; Yeju Yan; Jiangbing Qiu; Guowang Yan; Peng Zhao; Min Li; Ying Ji; Guixiang Wang; Fanping Meng; Yang Li; James S. Metcalf; Sandra A. Banack (Journal of Hazardous Materials, 2023)

Emergency responses to acrylonitrile maritime spills from the perspective of marine ecological protection - Xiaotong Wang; Fanping Meng (Frontiers in Marine Science, 2022)
The increases in chemical shipping volumes increase the risk of hazardous noxious substances (HNSs) spills at sea. As one of the most frequently transported HNSs, acrylonitrile (ACN) spill incidents occur from time to time. The spilled ACN will have a wide range of short-term and long-term impacts on the marine environment. To reasonably standardise and optimise the emergency response countermeasures for ACN spill and maintain marine ecological health, the marine ecological hazards and physico-chemical behaviours of ACN were summarised. Based on this, the emergency response countermeasures for ACN spill at sea were studied and summarised in five aspects: spill source control, rapid prediction, emergency monitoring, numerical simulation and impact assessment, and elimination of ACN. This review forms a set of systematic emergency response countermeasures for deployment in ACN maritime spill incidents.

Enhanced biodegradation of para-xylene by the marine cryptophyte Rhodomonas sp. JZB-2 by changing the concentrations of nutrients, iron, and vitamins - Jiaqi Liu; Shuhao Du; Fanping Meng; Dawei Li (Journal of Applied Phycology, 2022)

Comparative study on virus shedding patterns in nasopharyngeal and fecal specimens of COVID-19 patients - Ning Zhang; Yuhuan Gong; Fanping Meng; Yi Shi; Jun Wang; Panyong Mao; Xia Chuai; Yuhai Bi; Penghui Yang; Fusheng Wang (Science China Life Sciences, 2021)

Microalgal Cultivation in Secondary Effluents: Enhancement of Algal Biomass, Nutrient Removal, and Lipid Productivity - Bo Zhang; Fanping Meng; Hongwu Cui; Xiang Dou; Shuhao Du; Xiaoling Peng (Journal of Ocean University of China, 2020)

Effect of pH, Temperature, and CO2 Concentration on Growth and Lipid Accumulation of Nannochloropsis sp. MASCC 11 - Xiaoling Peng; Fanping Meng; Yuejie Wang; Xiaoyan Yi; Hongwu Cui (Journal of Ocean University of China, 2020)

Removal of phenol by Isochrysis galbana in seawater under varying temperature and light intensity - Hao Li; Fanping Meng; Yuejie Wang; Yufei Lin (Journal of Oceanology and Limnology, 2020)

Effects of two common antibiotics on the growth and lipid production of Tetradesmus obliquus cultivated in the effluent of municipal wastewater treatment plant - Shuhao Du; Xiang Dou; Fanping Meng; Xiaoling Peng (Journal of Applied Phycology, 2020)

Toxicological Assessment of Intermediates in Natural Attenuation of p-Xylene to Marine Microalgae - Feng Li; Weiyan Duan; Shuhao Du; Fanping Meng; Xiaoling Peng; Lihong Peng; Yufei Lin; Jiangyue Wu; Guoshan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Growth inhibition and oxidative stress in two species of marine diatoms exposed to 1-phenylethanol - Xiang Dou; Fanping Meng; Weiyan Duan; Qunqun Liu; Hao Li; Shuhao Du; Xiaoling Peng (Journal of Oceanology and Limnology, 2019)

Biodegradation of phenol by Isochrysis galbana screened from eight species of marine microalgae: growth kinetic models, enzyme analysis and biodegradation pathway - Yuejie Wang; Fanping Meng; Hao Li; Shilin Zhao; Qunqun Liu; Yufei Lin; Guoshan Wang; Jiangyue Wu (Journal of Applied Phycology, 2019)

Responses of a new isolated Cyanobacterium aponinum strain to temperature, pH, CO2 and light quality - Fanping Meng; Hongwu Cui; Yuejie Wang; Xianglei Li (Journal of Applied Phycology, 2018)

Application of sodium erythorbate to promote the growth of Chlorella vulgaris - Hongwu Cui; Fanping Meng; Feng Li; Yuejie Wang (Journal of Applied Phycology, 2017)